(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
The awareness of natural fibers as alternative materials to synthetic fibers in composite applications have increased briskly due to lightweight, non-toxic, low cost and abundantly available. To-date, there are still limited works on fully biodegradable composites also known as biocomposites, especially using long pineapple leaf fiber (PALF) reinforced poly lactic acid biocomposites. Thus, this study presents an investigation of the effects of alkaline treatment and use of different fiber length on the mechanical performance of pineapple leaf fibers reinforced poly lactic acid, biocomposites. Flexural testing was conducted via ASTM D790. The results showed enhancement in flexural properties of the biocomposites when the PALF fibers were treated with alkaline treatment, suggesting an effect of improving mechanical interlocking between matrix and reinforcement due to rougher fiber surface. The flexural strength and modulus of long treated fibers increased from 56.47 MPa and 4.24 GPa to 114.03 MPa and 5.70 GPa respectively compared to long untreated fibers. Â In addition, the effect of fiber length is also proven to affect the overall performance of the biocomposites, in which the long PALF fiber composites exhibit superior flexural properties to those of the short fiber reinforced PLA biocomposites, i.e. flexural modulus of 5.7 GPa and 0.22 GPa for the long fiber composites and short fiber composites respectively. The existence of sodium hydroxide, (NaOH) on PALF fibers were confirmed by FTIR analysis. Surface morphology of both untreated and treated samples was studied by using a scanning electron microscope (SEM). Results from both analyses suggest removal of lignin and hemicellulose on the alkaline-treated PALF fiber reinforced composites led to a rougher fibers surface and formed a better fiber-matrix adhesion, as reflected in the flexural properties of the biocomposites as reported above.